2007
DOI: 10.1159/000100083
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Combined with Vitamin A Synergizes to Increase Retinyl Ester Storage in the Lungs of Newborn and Dexamethasone-Treated Neonatal Rats

Abstract: Background: Retinyl esters (REs), the major storage form of vitamin A (retinol), provide substrates for the production of bioactive retinoids, including retinoic acid (RA), which are known to promote lung development and maturation. We previously showed that the nutrient-metabolite combination VARA (molar ratio 10 vitamin A to 1 RA), synergistically increased REs in the lungs of 1-week-old rats, compared to vitamin A or RA alone. Objectives: To test the hypotheses, first, that VARA is more effective in increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…For liver and lung tissues, a measured portion of the extract was taken for analysis of radioactivity by LSC and a portion was used for saponification and analysis of total retinol by UPLC. Previous studies have shown that, in liver and lung ( 18 , 19 , 21 ), >90% of total retinol is esterified and thus the values reported here for total retinol in these tissues represent mostly retinyl esters. For other tissues, all of the extract was evaporated to dryness and analyzed for 3 H radioactivity by LSC.…”
Section: Methodssupporting
confidence: 51%
“…For liver and lung tissues, a measured portion of the extract was taken for analysis of radioactivity by LSC and a portion was used for saponification and analysis of total retinol by UPLC. Previous studies have shown that, in liver and lung ( 18 , 19 , 21 ), >90% of total retinol is esterified and thus the values reported here for total retinol in these tissues represent mostly retinyl esters. For other tissues, all of the extract was evaporated to dryness and analyzed for 3 H radioactivity by LSC.…”
Section: Methodssupporting
confidence: 51%
“…The neonatal ages of observation were selected to represent the pre-, early, and mid-septation stages of postnatal lung development. As shown in Fig 1A , on the day of dosing (P1, P4, P7, P10 and 2 months), each pup received a single oral dose delivered directly into the mouth via a small micropipette, as previously described [ 4 6 ]. The volume of each dose was ~0.4 μL/g body wt adjusted after weighing.…”
Section: Methodsmentioning
confidence: 99%
“…It was discovered recently that vitamin A and all- trans -retinoic acid synergistically increase retinol uptake and retinyl ester storage in neonatal rat lung (James et al 2010; Ross and Ambalavanan 2007; Ross and Li 2007; Wu and Ross 2010) and antibody production by the spleen (Tan et al 2012). In addition to the ability of retinoic acid to stimulate STRA6 expression, the ability of exogenous retinoic acid to stimulate STRA6’s activity may contribute to enhanced retinoid uptake.…”
Section: Discussionmentioning
confidence: 99%